The assassin bug genera Nagustoides and Stenolemus (Hemiptera: Heteroptera: Reduviidae) newly recorded from Japan - Ishikawa, Tadashi; Naka, Takeru (Zootaxa, 2016)
Two assassin bug genera, Nagustoides Miller, 1954 of Harpactorinae and Stenolemus Signoret, 1858 of Emesinae (Hemiptera: Heteroptera: Reduviidae), are recorded from Japan for the first time, with the presence of the representative species N. lii Zhao, Cai & Ren, 2006 and S. alikakay Rédei & Tsai, 2010. Distribution ranges of the two species are revised by the present finding.